Queer Livability German Sexual Sciences and Life Writing - Linge, Ina (Social History, Popular Culture, And Politics In Germany, 2023)
This book brings together an exciting new archive of queer and trans voices from the history of sexual sciences in the German-speaking world. A new language to express possibilities of gender and sexuality emerged at the turn of the twentieth century, from Sigmund Freud's theories of homosexuality in Vienna to Magnus Hirschfeld's "third sex" in Berlin. Together, they provided a language of sex and sexuality that is still recognizable today. Queer Livability: German Sexual Sciences and Life Writing shows that individual voices of trans and queer writers had a significant impact on the production of knowledge about gender and sexuality during this time and introduces lesser known texts to a new readership. It shows the remarkable power of queer life writing in imagining and creating the possibilities of a livable life in the face of restrictive legal, medical, and social frameworks. Queer Livability: German Sexual Sciences and Life Writing will be of interest to anyone who wants to learn more about LGBTQ+ history and literature. It also provides a fascinating insight into the historical roots for our thinking about gender and sexuality today. The book will be of relevance to an academic readership of students and faculty in German studies, literary studies, European history, and the interdisciplinary fields of gender and sexuality studies, medical humanities, and the history of sexuality.